Some of the operands are missing (due to limitation of editor?) and hence assuming the equation is x^2+5x-5 = 0. The roots are
(-5 + sqrt(25+20))/2 and (-5 - sqrt(25+20))/2
(-5 + sqrt(45))/2 and (-5 - sqrt(45))/2
(-5 + 6.70)/2 and (-5 - 6.70)/2
(1.70)/2 and (-11.70)/2
0.85 and -5.85
If you mean: x2+5x+6 = 0 then the solutions are x = -3 and x = -2
X2 - 5X = 24 X2 - 5X - 24 = 0 (X - 8)(X + 3) X = 8 ----------------and X = - 3 --------------
x2 + 49 = 0 ∴ x2 = -49 ∴ x = 7i
x2 + 5x - 5 = 0 ∴ x2 + 5x + 25/4 = 45/4 ∴ (x + 5/2)2 = 45/4 ∴ x + 5/2 = ±√(45/4) ∴ x = -5/2 ± 3√(5)/2 ∴ x = (-5 ± 3√5)/2 ∴ x ∈ {(-5 - 3√5)/2, (-5 + 3√5)/2}
y + 5x = 6 if x = {-1, 0, 1}
x2-5x = 24 x2-5x-24 = 0 (x-8)(x+3) = 0 x = 8 or x -3
x2 - 5x + 6 = 0(x - 2) (x - 3) = 0x - 2 = 0 5 × 69 or x - 3 = 0x = 2 or x = 3
If you mean: x2+5x+6 = 0 then the solutions are x = -3 and x = -2
X2 - 5X = 24 X2 - 5X - 24 = 0 (X - 8)(X + 3) X = 8 ----------------and X = - 3 --------------
x2 + 49 = 0 ∴ x2 = -49 ∴ x = 7i
do it yourself
x2-5x = 0 x(x-5) = 0 x = 0 or x = 5
x2 + 5x - 5 = 0 ∴ x2 + 5x + 25/4 = 45/4 ∴ (x + 5/2)2 = 45/4 ∴ x + 5/2 = ±√(45/4) ∴ x = -5/2 ± 3√(5)/2 ∴ x = (-5 ± 3√5)/2 ∴ x ∈ {(-5 - 3√5)/2, (-5 + 3√5)/2}
y + 5x = 6 if x = {-1, 0, 1}
x2 - 5x = 0x (x - 5) = 0x = 0andx = 5
x2 + 5x + 3 = 9 x2 + 5x - 6 = 0 (x + 6)(x - 1) = 0 x = -6 or x = 1
x2+4x-9 = 5x+3 x2+4x-5x-9-3 = 0 x2-x-12 = 0 (x+3)(x-4) = 0 x = -3 or x = 4